Measurement invariance of the patient health questionnaire‐9 (PHQ‐9) depression screener in U.S. adults across sex, race/ethnicity, and education level: NHANES 2005–2016. Issue 9 (29th July 2019) - Patel, Jay S.; Oh, Youngha; Rand, Kevin L.; Wu, Wei; Cyders, Melissa A.; Kroenke, Kurt; Stewart, Jesse C.
Abstract : Background: Despite its popularity, little is known about the measurement invariance of the Patient Health Questionnaire‐9 (PHQ‐9) across U.S. sociodemographic groups. Use of a screener shown not to possess measurement invariance could result in under/over‐detection of depression, potentially exacerbating sociodemographic disparities in depression. Therefore, we assessed the factor structure and measurement invariance of the PHQ‐9 across major U.S. sociodemographic groups. Methods: U.S. population representative data came from the 2005–2016 National Health and Nutrition Examination Survey (NHANES) cohorts. We conducted a measurement invariance analysis of 31, 366 respondents across sociodemographic factors of sex, race/ethnicity, and education level. Results: Considering results of single‐group confirmatory factor analyses (CFAs), depression theory, and research utility, we justify a two‐factor structure for the PHQ‐9 consisting of a cognitive/affective factor and a somatic factor (RMSEA = 0.034, TLI = 0.985, CFI = 0.989). On the basis of multiple‐group CFAs testing configural, scalar, and strict factorial invariance, we determined that invariance held for sex, race/ethnicity, and education level groups, as all models demonstrated close model fit (RMSEA = 0.025–0.025, TLI = 0.985–0.992, CFI = 0.986–0.991). Finally, for all steps ΔCFI was <−0.004, and ΔRMSEA was <0.01. Conclusions: We demonstrate that the PHQ‐9 is acceptable to use in major U.S. sociodemographic groups and allows for meaningful comparisons in total, cognitive/affective, and somatic depressive symptoms across these groups, extending its use to the community. This knowledge is timely as medicine moves towards alternative payment models emphasizing high‐quality and cost‐efficient care, which will likely incentivize behavioral and population health efforts. We also provide a consistent, evidence‐based approach for calculating PHQ‐9 subscale scores.